Quantum Chemical Calculations of Warfarin Sodium, Warfarin and Its Metabolites (Communications in Computational Physics, 2008)
The structural, vibrational and electronic properties of warfarin sodium, warfarin and its metabolites have been investigated theoretically by performing the molecular mechanics (MM+ force field), the semi-empirical self-consistent-field molecular-orbital (AM1), and density functional theory calculations. The geometry of the molecules have been optimized, the vibrational dynamics and the electronic properties of the molecules have been calculated in their ground state in gas phase.